(f+g)(x) = f(x) + g(x)
(f+g)(x) = 3x-2 + 2x+1
(f+g)(x) = (3x+2x) + (-2+1)
(f+g)(x) = 5x - 1
Hey!
Your answer is solved below/above idk wherever just see in the picture.
Answer:
<h2>x = 28</h2>
Step-by-step explanation:
ΔARP and ΔCRD are similar. Therefore the sides are in proportion:

We have:
AR = 10 + x
CR = x
PR = 15 + 42 = 57
DR = 42
Substitute:
<em>cross multiply</em>
<em>use distributive property</em>

<em>subtract 42x from both sides</em>
<em>divide both sides by 15</em>

If you count the zeros it’s
one billionth